2006
DOI: 10.1063/1.2207927
|View full text |Cite
|
Sign up to set email alerts
|

The Supernova Gamma-Ray Burst Connection

Abstract: ABSTRACT:Observations show that at least some gamma-ray bursts (GRBs) happen simultaneously with core-collapse supernovae (SNe), thus linking by a common thread nature's two grandest explosions. We review here the growing evidence for and theoretical implications of this association, and conclude that most long-duration soft-spectrum GRBs are accompanied by massive stellar explosions (GRB-SNe). The kinetic energy and luminosity of well-studied GRBSNe appear to be greater than those of ordinary SNe, but evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 204 publications
(160 reference statements)
2
17
0
Order By: Relevance
“…The connection between long-duration GRBs and SNe was predicted theoretically [56,57] and has been verified observationally through detecting spectroscopic features of the underlying SNe in some nearby GRBs [4]. Their host galaxies are typically irregular (in a few cases spiral) galaxies with intense star formation [58].…”
Section: Long Vs Short/type I Vs Type Iimentioning
confidence: 97%
See 3 more Smart Citations
“…The connection between long-duration GRBs and SNe was predicted theoretically [56,57] and has been verified observationally through detecting spectroscopic features of the underlying SNe in some nearby GRBs [4]. Their host galaxies are typically irregular (in a few cases spiral) galaxies with intense star formation [58].…”
Section: Long Vs Short/type I Vs Type Iimentioning
confidence: 97%
“…It has been speculated that long GRBs are associated with the deaths of massive stars and hence SNe [4]. The connection between long-duration GRBs and SNe was predicted theoretically [56,57] and has been verified observationally through detecting spectroscopic features of the underlying SNe in some nearby GRBs [4].…”
Section: Long Vs Short/type I Vs Type Iimentioning
confidence: 97%
See 2 more Smart Citations
“…On one hand, with firmed detections of GRB-supernovae connections for four nearby cases [13][14][15][16][17] , it is now generally accepted that long GRBs are associated with energetic core-collapse supernovae [18,19] (see a recent review by Woosley et al [20] ). Interestingly, Li [21] found that the peak spectral energy of GRBs is correlated with the peak bolometric luminosity of the underlying supernovae (SNe), based on the four pair GRB-SNe connections.…”
mentioning
confidence: 98%